Inventing Exceptional Religion: U.S. Catholics and Cognitive Disability in Postwar America - Walker-Cornetta, Andrew (US catholic historian, 2024)
After the Second World War, U.S. Catholics invented what this article identifies as “exceptional religion.” This invention entailed two interrelated projects: 1) efforts to prepare people with cognitive disabilities for First Communion and 2) efforts to represent such persons as uniquely powerful spiritual beings within broader economies of the sacred. Exploring the postwar emergence of new catechetical materials aimed at so-called “exceptional children” and depictions of people with cognitive disabilities in various Catholic media, this article demonstrates the importance of these forms of difference to the making and re-making of U.S. Catholicism in a wider moment of social change. The end of the essay turns to interrogate the impacts of this invention on the lives of the persons it identified and those close to them.